(untitled) (Ecological Bulletin of Kryvyi Rih District, 2019)
The results of research of morphological signs of vegetative and generative plant organs of introduced species: Canna indica L., C. iridiﬂora Ruiz., C. edulis Ker-Cawl., C. gigantean Desf, C. ﬂacida Salisd and 37 varieties of foreign and native selection from the collection of KryvyiRih Botanical Garden of National Academy of Sciences of Ukraine are given. The most informative for determination of plant’s decorativeness: total height and height of an inﬂorescence, diameter of a ﬂower, color of a leaf are singled out from the complex of described morphological features of vegetative and generative organs of the investigated varieties and species of canna. The estimation of the decorative potential of plant genus Canna L. is given according to morphological and the most promising introduents for introduction into practice of green building of the regionare highlighted. A variety of promising cultivars of Canna L. genus for the design of KryviyRihhas been developed and proposed according to long research’s results.